Warrior for Climate Science and Awareness: Stephen Schneider. (April 2013) - Chadwick, Sarah Jo; Armel, Carrie; Root, Terry; Crookall, David
This tribute outlines some of the major contributions that Stephen H. Schneider made to climate change science and to communication about that science to help a broader audience understand it in an educated manner, and realize that urgent decisions are needed, even with incomplete information. We highlight some of the awards and honors that Dr. Schneider received, and quote from a few already published tributes. We cite some of his publications and provide further sources for readers to learn more about climate science and about Dr. Schneider.